2020
DOI: 10.3390/w12092379
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Flooding Risk Assessment Using a GIS-Based Spatial Multi-Criteria Decision Analysis Approach

Abstract: Coastal areas are expected to be at a higher risk of flooding when climate change-induced sea-level rise (SLR) is combined with episodic rises in sea level. Flood susceptibility mapping (FSM), mostly based on statistical and machine learning methods, has been widely employed to mitigate flood risk; however, they neglect exposure and vulnerability assessment as the key components of flood risk. Flood risk assessment is often conducted by quantitative methods (e.g., probabilistic). Such assessment uses analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 82 publications
3
18
0
Order By: Relevance
“…Moreover, the high risk of urban floods in Peshawar city could be attributed to rapid urbanization, high population growth, degraded environment, lack of advanced early warning mechanism, low public awareness, and lack of adaptive capacity. Similar findings were reported by previous studies related to vulnerability assessment [38,39,44], which found that proper early warning system, high preparedness level, good economic status, better employment, multiple sources of income, and social networks or participation of people in intra community activities play a significant role in enhancing capacities of the local communities to cope effectively with floods.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the high risk of urban floods in Peshawar city could be attributed to rapid urbanization, high population growth, degraded environment, lack of advanced early warning mechanism, low public awareness, and lack of adaptive capacity. Similar findings were reported by previous studies related to vulnerability assessment [38,39,44], which found that proper early warning system, high preparedness level, good economic status, better employment, multiple sources of income, and social networks or participation of people in intra community activities play a significant role in enhancing capacities of the local communities to cope effectively with floods.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of enough coping capacity in the above-mentioned parts highlights the strong economic status, organized institutional setup and high literacy/awareness level. Similar findings were reported by various studies related to vulnerability assessment [38,39,44,68], which found that proper early warning system, high preparedness level, good income status, better employment, multiple sources of income, and social networks or participation of people in intra community activities play a significant role in enhancing capacities of the communities to cope effectively with floods.…”
Section: Coping Capacity (I CC )supporting
confidence: 86%
See 1 more Smart Citation
“…Hazard assessment has been conducted in many different areas including coastal regions, with a pronounced focus on hydrometeorology hazards such as cyclones, storm surges, and flooding. Flood hazard measurement aims to identify the flood pattern utilizing relevant parameters such as inundation depth [36][37][38], flood duration [38][39][40], and even timing of flooding [41][42][43]. This information can be extracted through hydraulic models with different scenarios [44] or based on past recorded events [45,46].…”
Section: Hazard (H)mentioning
confidence: 99%
“…Because the System has a trivial solution, (1) must be a singular matrix. Being (3) an equation of degree n, called the characteristic equation of M, which is equal to 0 if λ is replaced by M, producing a matrix equation, where the roots are the characteristic values that were obtained from the priority vector, from of the solution of the corresponding systems of equations [42], [43].…”
mentioning
confidence: 99%